2014 Fourth International Conference on Digital Information and Communication Technology and Its Applications (DICTAP) 2014
DOI: 10.1109/dictap.2014.6821701
|View full text |Cite
|
Sign up to set email alerts
|

Elderly care notification system using hand posture recognition

Abstract: This paper proposes a hand posture recognition as an assistive tool for elderly care. The system uses Haar-like feature, Principle Component Analysis (PCA), and simulation web server for detection, recognition, and alert by order. Our system interprets the hand sign captured by web camera and alerts a caregiver via smart phone. Besides, a caregiver can also periodically check needs of an elder from a smart phone. So a caregiver can do other tasks more efficiently because he/she need not to be with an elder at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We found that 4 of the 7 compared works use video/image capture [27,29,30,33] for gesture recognition. Although these systems have high percentages of accuracy in gesture recognition, they also raise several issues and constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 4 of the 7 compared works use video/image capture [27,29,30,33] for gesture recognition. Although these systems have high percentages of accuracy in gesture recognition, they also raise several issues and constraints.…”
Section: Discussionmentioning
confidence: 99%
“…These solutions typically use sensors, computers, mobile devices, telehealth systems and rely on wireless and cloud computing technologies [26]. In this sense, several gesture-based contactless solutions were proposed for ill, disable or senior people [27,28,29]. Most of the solutions use cameras for gesture recognition.…”
Section: Related Workmentioning
confidence: 99%
“…An assistive hand posture recognition system for elderly care is proposed in [9]. The system uses Haar-like feature, Principal Component Analysis (PCA), and simulation web server for detection, recognition, and alert by order.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], a prototype system of fall detection application designed for smart phone is proposed. Sawasdee et al [21] propose a hand posture recognition as an assistive tool for elderly care. In [22], a drowsy driver detection system has been developed, using video processing analyzing eyes blinking concepts for measuring eyes closure duration and head posture estimation to verify the driver vigilance state.…”
Section: Related Workmentioning
confidence: 99%